2002
DOI: 10.1007/bf02492009
|View full text |Cite
|
Sign up to set email alerts
|

Micellar electrokinetic capillary chromatography as an alternative method for determination of hydrocortisone and its most important associated compounds in local pharmaceutical preparations

Abstract: SummaryA new, simple, and accurate micellar electrokinetic chromatographic (MEKC) method is clescribed for quantification of hydrocortisone, hydrocortisone hemisuccinate, hydrocortisone acetate, nystatin, oxytetracychne, Zn-bacitracin, polymyxin B, and hdocaine in ocular and cutaneous pharmaceutical products. The separation was performed at 25 ~ and 25 kV, with 15 mM phosphate + 15 mM borate buffer, pH 8.2, and 60 mM sodium dodecylsulfate (SDS) in 10:1 (%, v/v) methanol-water as background electrolyte. Under t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 28 publications
0
18
0
Order By: Relevance
“…The LOQs were 19.0 mg/L for polymyxin, 8.5 mg/L for bacitracin and 6.5 mg/L for oxytetracycline. It was demonstrated that this method could be used for the analysis of eardrops, ointments and tablets containing bacitracin, polymyxin, oxytetracycline and/or other components; however, it was acknowledged that the extraction step was not optimized for each product [25].…”
Section: Polypeptidesmentioning
confidence: 99%
See 3 more Smart Citations
“…The LOQs were 19.0 mg/L for polymyxin, 8.5 mg/L for bacitracin and 6.5 mg/L for oxytetracycline. It was demonstrated that this method could be used for the analysis of eardrops, ointments and tablets containing bacitracin, polymyxin, oxytetracycline and/or other components; however, it was acknowledged that the extraction step was not optimized for each product [25].…”
Section: Polypeptidesmentioning
confidence: 99%
“…Prednisolone, prednisolone acetate, zinc bacitracin, sulfacetamide sulfate, phenylephrine and naphazoline nitrate were separated in a 5 mM phosphate-5 mM borate buffer, pH 8.2, containing 50 mM SDS and 3% v/v CH 3 CN, with detection at 205 nm. For sulfacetamide, the method is linear from 0.3 to 32.0 mg/mL, with an LOQ of 0.3 mg/mL, and an LOD of 0.09 mg/mL [25]. The determination of the amount of sulfacetamide present in both eye drops and ointment was demonstrated [25].…”
Section: Sulfonamidesmentioning
confidence: 99%
See 2 more Smart Citations
“…The methods reported for HYD such as UV spectrophotometry 14 , HPLC [15][16][17] , micellar electrokinetic capillary chromatography 18,19 and capillary electrophoresis 20 . Simultaneous determination of CIP and HYD has been reported in the literature by HPLC method 21 and chemometric method 22 .…”
Section: Introductionmentioning
confidence: 99%